Clinical manifestation, diagnosis, management, and treatment outcome of pericarditis in patients with systemic lupus erythematosus - Tanas Buppajarntham (2018)
© 2014, Medical Association of Thailand. All rights reserved. Objective: To investigate the clinical manifestations, diagnosis, etiology, management, and outcomes of patients with systemic lupus erythematosus (SLE) and pericarditis Material and Method: The authors retrospectively reviewed the records of 81 patients who were diagnosed of SLE according to the American College of Rheumatology criteria and had 82 episodes of pericarditis between 2002 and 2010. The diagnosis of pericarditis was defined as the presence of pericardial effusion alone by echocardiography or having 2 out of 4 of the following criteria: retrosternal pain, pericardial friction rub, widespread ST-segment elevation, and new/worsening pericardial effusion. Results: Most of them (92%) were female with the median disease duration (range) of 1 (0-312) month. Cardiac tamponade occurred in 16% (95% CI 8.72-25.58%). There was no statistically significant difference between patients who developed tamponade and those who did not. The causes of pericarditis included active SLE (93%), and suspected tuberculosis (TB) (5%), with 2% inconclusive. In patients with lupus pericarditis, 71% had other active organ involvement. Most lupus pericarditis patients (79%) had good response to steroid or NSAIDs. Diagnosis of TB pericarditis was made by clinical suspicion without microbiological or pathological evidence. Conclusion: In an endemic area of TB, lupus pericarditis was still the most common cause of pericarditis in SLE. Most patients responded well to steroid.